Prenatal Radiation Exposure: Dose Calculation - Scharwächter, C.; Röser, A.; Schwartz, C. A.; Haage, P. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
The unborn child requires special protection. In this context, the indication for an X-ray examination is to be checked critically. If thereupon radiation of the lower abdomen including the uterus cannot be avoided, the examination should be postponed until the end of pregnancy or alternative examination techniques should be considered. Under certain circumstances, either accidental or in unavoidable cases after a thorough risk assessment, radiation exposure of the unborn may take place. In some of these cases an expert radiation hygiene consultation may be required. This consultation should comprise the expected risks for the unborn while not perturbing the mother or the involved medical staff. For the risk assessment in case of an in-utero x-ray exposition deterministic damages with a defined threshold dose are distinguished from stochastic damages without a definable threshold dose. The occurrence of deterministic damages depends on the dose and the developmental stage of the unborn at the time of radiation. To calculate the risks of an in-utero radiation exposure a three-stage concept is commonly applied. Depending on the amount of radiation, the radiation dose is either estimated, roughly calculated using standard tables or, in critical cases, accurately calculated based on the individual event. The complexity of the calculation thereby increases from stage to stage. An estimation based on stage one is easily feasible whereas calculations based on stages two and especially three are more complex and often necessitate execution by specialists. This article demonstrates in detail the risks for the unborn child pertaining to its developmental phase and explains the three-stage concept as an evaluation scheme. It should be noted, that all risk estimations are subject to considerable uncertainties. • Radiation exposure of the unborn child can result in both deterministic as well as stochastic damage und hitherto should be avoided or reduced to a minimum.• In case of radiation a suitable hygiene consultation may be necessary.• For risk assessment a three-stage concept is applied, which, depending on the radiation exposure, estimates or calculates the dose for the unborn child.• The radiologist plays a crucial role as a competent advisor and provider of reliable expert information.Citation Format:• Scharwächter C, Röser A, Schwartz CA et al. Prenatal Radiation Exposure: Dose Calculation. Fortschr Röntgenstr 2015; 187: 338 – 346
Keywords: health policy and practice; radiation effects; radiation safety; pregnancy